PENGEMBANGAN INSTRUMEN PENILAIAN PSIKOMOTORIK MATERI IDENTIFIKASI LOGAM MERKURI DALAM PRODUK KOSMETIK - Handayani, Yuni Rahmawati; Muhairini, Rini; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to determine the level of feasibility and response of students to psychomotor assessment instruments of mercury metal identification material in cosmetic products. This research uses development research method (Development Researct) which refers to the Borg Gall model. The subject of this study was a psychomotor assessment instrument of mercury metal identification material in cosmetic products and the test subject was a student of chemistry education FKIP Untan Pontianak. Due diligence is tested based on content, language, and presentation aspects. The feasibility test results on each aspect with the criteria are very feasible with an average score of 90.20%. Based on the results of the questionnaire calculation of student response to this assessment instrument, shows that the results of the initial field test and the main field test get the percentage of the average score in a row 81.3% and 85.3% with the category of assessment criteria is very high. Thus, psychomotor assessment instruments of mercury metal identification material in cosmetic products can be used as analytical chemical preticum research instruments I.